Landscape analysis of matrix metalloproteinases reveals key prognostic markers for prostate cancer - Li, Wei; Wei, Xi; Yu, Ying; Tian, Yuan; Yu, Qi; Qiao, Jun; Tao, Yuewei; Li, Yanfeng; Li, Tao (Frontiers in Immunology, 2025)
BackgroundProstate cancer (PCa) is the most common male malignancy and significantly impairs patient’s survival. Matrix metalloproteinases (MMPs) play a crucial role in tumor progression, yet the comprehensive role of MMPs in PCa remains unclear.MethodData from UCSC and GEO databases were firstly analyzed to evaluate expression characteristics, prognostic value, immune-cell infiltration, tumor-mutation burden (TMB), microsatellite-instability (MSI), immunotherapy sensitivity, and drug sensitivity in PCa. COX-regression analysis was utilized to identify MMPs that affected (Disease-free survival) DFS. Various cellular functional experiments and conditional medium cultivation system were utilized to verify the effect of MMP11 on PCa cells. Subsequently, single-cell transcriptome and spatial-transcriptome data was analyzed to explore the regulatory effect of MMP11 on microenvironment.ResultMost MMPs exhibit differential expression between tumor and normal tissues, with specific MMPs correlating with pathological features of PCa. Among 24 MMPs analyzed, MMP11 was uniquely associated with shorter DFS. High MMP11 expression correlated with increased infiltration of regulatory Tregs and M2 macrophages, elevated immune checkpoint molecule expression, higher TMB, MSI, and enhanced immunotherapy sensitivity. MMP11 suppression inhibited PCa cell proliferation, migration, invasion, and epithelial-mesenchymal transition.MMP11 was predominantly expressed in fibroblasts and linked to the establishment of an immunosuppressive tumor microenvironment. Targeting MMP11 in cancer-associated fibroblasts reversed their pro-tumorigenic effects on PCa progression. Finally, MMP11 is broadly upregulated across malignancies and associated with poor prognosis in multiple cancer types.ConclusionThis study comprehensively explored the role of MMPs in PCa. Noteworthy, we further proved that MMP11 significantly promoted PCa probably through reprogramming of tumor microenvironment, which might provide a promising-target for PCa treatment.